National survey on direct employment in the Colombian oil palm sector - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma (Federación Nacional de Cultivadores de Palma de Aceite, 2020)
This book is a compendium of the efforts of various actors and aims to reach a broader scope, inspiring other sectors and making that the results here shown become input for decision-making processes in rural areas of our country.
Keywords: Agroindustria de la palma de aceite; Empleo; Empleo verde; Responsabilidad social